MERDEKA BELAJAR-KAMPUS MERDEKA IN DEVELOPING BUSINESS THE ANALYSIS OF A POLICY IMPLEMENTATION: SLUM FREE URBAN PROGRAM (KOTAKU) IN BINJAI CITY - Khaira Zakya; R Hamdani Harahap; Sakhyan Asmara (Bajang Institute, 2021)
Slum-free Urban Program (KOTAKU) is arranged by the Directorate General of Human Settlements, Presidential Regulation Number 2 of 2015, which instructs the development and expansion of urban regions by handling the residential environment's quality. The research shows that Binjai City has 21 Urban Villages included in the slums residential area. They are Tanah Merah, Bhakti Karya, Tanah Seribu, Puji Dadi, Binjai Estate, Rambung Barat, Rambung Timur, Timbang Langkat, Sumber Mulyorejo, Sumber Karya, Bandar Sinembah, Limau Mungkur, Paya Roba, Suka Maju, Suka Ramai, Tangsi, Satria, Berngam, Pekan Binjai, Damai, and Cengkeh Turi. The KOTAKU program gets its fund from the Kotaku program, Regional Budget (APBD), and communities' funds to manage the program. In this research, the methodology used was the descriptive method using a qualitative approach to focus on the current issues or phenomena during the research. The research shows the decrease of slums residential area from 315.6 Ha to 224.57 Ha. The implementation of the KOTAKU program has a resistor factor: the lack of socialization from the government regarding the program and the lack of community participation in the development process. This research concludes that the implementation of the KOTAKU program in Binjai City has corresponded to the local people requirements, and it creates a decrease of residential slums area to 30%. This research provides a recommendation: the government needs to make more socialization regarding the program and conduct direct coordination to the community to increase people's participation to run the KOTAKU program. The suggestion for future research is to conduct a bottom-up strategy so that many people are actively involved in the program